Inflation, Inflation Uncertainty and Economic Growth in Tunisia: Nonlinear Modelling Framework - Boujelbène, Thouraya; Ben Jedidia, Khoutem (Naše gospodarstvo/Our economy, 2025)
Inflation uncertainty is a critical factor influencing not only the market mechanisms but also the economic activity efficiency. In this paper, we investigated the relationship between inflation and growth to capture the impact of inflation uncertainty in Tunisia. The study relied on a dataset covering the period 1984.01-2018.08 and was characterized by a nonlinear specification. We used Hansen’s (2001) Threshold Regression (TR) analysis to determine one threshold effect of inflation on growth while explaining the role of inflation uncertainty in the whole process. This study concluded that an optimal inflation rate does exist. Under this rate, a little rise in inflation may enhance economic growth, allowing an adverse impact of inflation uncertainty. Above the critical threshold of 3%, it was revealed that inflation and inflation uncertainty play opposite roles: while the former harms growth, the latter benefits it. Thus, we cannot sustain the Friedman-Ball hypothesis for the two regimes. To the best of the authors’ knowledge, this is the first study that aimed to investigate the simultaneous effects of inflation and inflation uncertainty on growth in Tunisia using a non-linear methodology. This study aims to fulfil the knowledge gap of such studies for developing countries.
Keywords: Threshold regression model; Inflation; Inflation uncertainty; Economic growth; Tunisia